Sistemas agrários e agricultura no Alto Jequitinhonha, Minas Gerais - Silva, Daniel Ferreira da (2014)
The proposal of this thesis is to investigate, from the analysis of agrarian systems, the composition of the agricultural income of the major production systems of the Alto Jequitinhonha. With this purpose a characterization of the agrarian system at the regional level of the Alto Jequitinhonha was made, by identifying and characterizing the historical process of composition of public policies and agriculture; for these were analyzed the technical careers, income levels and the accumulation of production systems in the dynamics of the agrarian system of the upper Jequitinhonha - with emphasis on the city of Capelinha in Minas Gerais. This study is linked to the identification of factors that foment the accumulation process of a region, the role of public policies in boosting the agricultural systems and modeling of production systems as a tool for planning and intervention development agents, researchers and farmers. As a result, it appears that the territory called Alto Jequitinhonha is a region that encompasses several micro, typologies of farms and production systems, due to its historical and edaphoclimatic issues. It was noticed, throughout the work, under the economic point of view, that aimed at strengthening family agriculture, public policies have not only a compensatory character in front of the main agricultural activities practiced in the Alto Jequitinhonha. Although they were found in a more detailed study of Capelinha`s city, whose agriculture is of significant importance to the region, the typologies of agricultural enterprises, establishments and family employer, in addition to small farms and properties under the management of rural retirees, were analyzed in this thesis production systems found in the categories of family farmers employers and due to their socioeconomic importance. Thus, it was possible to observe the vegetable production and the white farming (maize, cassava and beans) in the properties, in addition to coffee, forestry and dairy cattle, of Capelinha, composing thus virtually all major products developed in Alto Jequitinhonha. Despite the intervention of the State to encourage the planting of eucalyptus and coffee throughout the 1970s and 1980s, the family agriculture created its own dynamic, incorporating stimulus of the State, without, however, changing its characteristics of productive diversification, and historically constructed socially and environmentally. Finally, it was observed that the strategies of farmers in the municipality of Capelinha reconcile, in its properties, commercial agricultural crops with other agricultural activities for self, added access to agricultural credit policies and especially marketing, allowed these mini-farms, to become economically viable.